A internacionalização do ensino superior na Universidade Federal de São Paulo: o programa ciência sem fronteiras na graduação em saúde - Timóteo, Varner [UNIFESP] (2017)
Introduction: The internationalization of education has been seen as a priority for many Higher Education Institutions (HEIs) in the world scenario. It means a series of international activities, such as academic mobility of students and teachers, partnerships for project development, creation of new academic joint research programs. Among the internationalization initiatives is the Science without Borders Program (CsF), regulated by Decree No. 7642, of December 13, 2011. At UNIFESP, this Program presents a continuous flow to undergraduate students and within their areas Priority areas, the areas of Health Sciences and Biomedical, Pharmaceutical, Biotechnology and Biodiversity that include Campi de São Paulo, Baixada Santista and Diadema stand out. Objectives: To investigate the internationalization process of undergraduate health students under the CsF Program. Analyze specifically, the reasons that motivate the students to carry out an international exchange, to identify the main obstacles that the student of the health area finds in the process of experience provided by the exchange, to know the contributions and benefits in the vision of that student and to map the suggestions of the students. Students to improve the internationalization process. Method: With a quantitative and qualitative exploratory approach, the study was conducted at UNIFESP with the participation of 94 students from the health area of Campi São Paulo, Diadema and Baixada Santista, who were scholarship holders of the Program between 2011 and 2015, respecting all the Ethical precepts of research. The data collection instrument used in the research was composed of three parts: a sociodemographic information form of the study population, a Likert-type attitudinal scale and two open questions. The assertions were analyzed statistically and the open questions were submitted to an analysis of content thematic modality. Results: UNIFESP students participating in the CSF Program are already proficient in the language of the country chosen for the exchange, they show great expectations regarding the possibility of an international exchange, idealizes several possibilities with the exchange (such as thinking about their professional future), the experience, in another country, time away from family, among other factors. The family is considered very important in the decision to participate in an exchange as well as the financial factor. The students report difficulties in communicating with SRI and the information disclosed in the selection bids, alleging a high cost of preparation with documents for the exchange. Emphasize that the subjects taken abroad need to be incorporated into the students' academic records. They emphasize that the program provides a differential in their professional life and suggests the improvement of the process of candidate selection, establishing clearer and more transparent rules of information, improving support before the exchange, during selection, after-selection and for His return to UNIFESP. Conclusions: The UNIFESP health students had an excellent expectation of participating in an international exchange through the CsF Program. The obstacles encountered in the exchange process allowed us to conclude that, 94% of the students had some difficulty in locating the information of the Program available by UNIFESP. And that more than 95% of the students the results of the exchange was satisfactory. We conclude that some actions should be provided for the good development of the process as the reduction of bureaucracy. This research did not pretend to exhaust this theme so relevant to the improvement of the Brazilian students' education. We understand that internationalization and especially the CsF Program require more studies with which we hope to contribute with this internationalization analysis at the Federal University of São Paulo.